(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Vridh Awsatha compared with Geriatric Population is the state of “Vata Vridhi” related with various Vatavridhi disorders. The older individuals often suffer from multiple medical problems. Like, osteoarthritis, shortness of breath, congestive heart failure, all can lead to difficulty with sleep initiation and maintenance. Trouble with sleep is strongly correlated with complaints about health and depression. Studies examining the prevalence of sleep disturbances in patients with chronic medical diseases have reported that 31% of arthritis and 66% of chronic pain patients report difficulty falling asleep, while 81% of arthritis, 85% of chronic pain, and 33% of diabetes patients report difficulty staying asleep. In a recent National Sleep Foundation survey of adults aged 65 years and over, those with more medical conditions, including cardiac and pulmonary disease and depression, reported significantly more sleep complaints. Objective: This study has been conducted to evaluate the sleeping and waking time of elderly and Diseases pattern with sleep status. Methodology: Interview based Questionnaire was prepared to know the sleep timings, waking up timings of elderly. 96 subjects of both sex was selected from OPD of AIIA, and nearby place and collected data was analyzed by using odd’s. Conclusion: According to the study the health status is directly affected by the timings of sleeping and waking up i.e. people who wake up early tends to be healthier. So, to add the quality in the end years of life, sleep will be main domain to work upon.